Boxwood Leafminer Monarthropalpus flavus (Schrank) (Insecta: Diptera: Cecidomyiidae) - Balwinder Kaur; Adam Dale (EDIS)
Boxwood leafminer, Monarthropalpusi flavus Schank (Diptera: Cecidomyiidae), is a gnat-like fly whose larvae can cause severe damage to boxwood (Buxus spp.) trees and shrubs across the United States. This small fly is native to Europe and was first detected as a pest of boxwood in the United States in 1910. This insect can cause serious damage to boxwood species, which are among the most commonly planted landscape ornamental plants in the eastern U.S. This document describes the boxwood leafminers biology, identification, and management.